Clinical and genetic findings in Hungarian patients with X-linked juvenile retinoschisis - Lesch, B; Szabó, V; Kánya, M; Somfai, G M; Vámos, R; Varsányi, B; Pámer, Zs; Knézy, K; Salacz, Gy; Janáky, M; Ferencz, M; Hargitai, J; et al. (Molecular vision, 2008)
To determine clinical phenotypes, examine the age dependency of X-linked juvenile retinoschisis (XLRS), and identify mutations in the retinoschisis1 gene (RS1) in 13 Hungarian (Caucasian) families with this disease. This study included 72 members in 13 families. Complete ophthalmological examinations, including optical coherence tomography (OCT) and full-field and multifocal electroretinography (ERG), were performed on 20 affected males, 13 female carriers, and 27 healthy controls. The patients were divided into two age groups (Group I <25 years and Group II >25 years), retrospectively, to assess the possible effects of age. Correlations among genotype, age, best corrected visual acuity (BCVA), OCT, and ERG results were analyzed. A modified classification scheme was done to identify the different phenotypes of the disease. In each of the 72 family members and 100 age-matched male controls, all exons and introns of RS1 were amplified by polymerase chain reaction (PCR) and directly sequenced. Foveal retinoschisis was detected in 25 eyes (62.5%) of patients by funduscopy, and in 29 eyes (72.5%) by OCT, while macular lamellar schisis was recognizable only by OCT in 30 eyes (75%) of patients. Foveal thickness (FT) and total macular volume were significantly increased in younger (Group I) patients only. For patients younger than 26 years, large inner nuclear central cysts were observable by OCT, while after 26 years, foveas were atrophic. White flecks and dots, which were like that seen in fundus albipunctatus, were detected in both eyes of one patient. In both patient groups, characteristically decreased b-waves of standard combined ERG were recorded without any significant difference between the patient groups. The BCVA and ERG parameters of all patients and the OCT of younger patients were significantly worse (p<0.05) than those of age-matched controls. A significant difference between the two age groups was found in case FT, total macular volume, and amplitudes of rod b-wave only. Moderate negative correlation (r=-0.54, p<0.001) was detected between age and FT, while only low negative correlation (r=-0.33, p<0.05) was detected between age and standard combined b-wave amplitudes of full-field ERG. BCVA LogMAR did not show any obvious correlation with age (r=-0.14, p=0.39) or with the type of mutation. Nine different mutations were identified in 25 male patients and 31 female carriers of 13 families: six known and one novel missense mutation (c.575C>T, p.Pro192Leu), one insertion mutation (c.579dupC, p.Ile194Hisfs29ext43), and one frameshift, causing splice site mutation (c.78+1G>C) were detected. These mutations were absent in the 100 age-matched male control samples. Foveal cystic schisis was found more often by OCT than by funduscopy (+10%), while flat macular lamellar schisis was recognizable only by OCT. Advancing age inversely influenced the size of cavities (FT), and standard combined b-wave amplitudes of full-field ERG, while BCVA, response density, and implicit times of multifocal electroretinography did not show any obvious correlation with age. The atrophic stage of the disease was observable after 26 years of age. The lesions that appeared to be indicative of fundus albipunctatus were proven to be palisades between the splitted retinal layers. Our modified classification scheme was helpful in assessing the prevalence of disease types. In these Hungarian patients, one novel and eight known mutations were detected. The distribution of mutations in RS1 was different to that reported in the literature, because the greatest number of different mutations was in exon 6 instead of exon 4. Two mutation hot spots were found: between c.418-422 in exon 5 and between c.574-579 in exon 6. Genotype-phenotype correlation was not demonstrable.